Hydroxytyrosol stimulates neurogenesis in aged dentate gyrus by enhancing stem and progenitor cell proliferation and neuron survival. Issue 3 (6th February 2020) - D'Andrea, Giorgio; Ceccarelli, Manuela; Bernini, Roberta; Clemente, Mariangela; Santi, Luca; Caruso, Carla; Micheli, Laura; Tirone, Felice
Abstract: The dentate gyrus of the hippocampus is one of two brain areas generating throughout life new neurons, which contribute to the formation of episodic/associative memories. During aging, the production of new neurons decreases and a cognitive decline occurs. Dietary factors influence neuronal function and synaptic plasticity; among them the phenolic compound hydroxytyrosol (HTyr), present in olive oil, displays neuroprotective effects. As age impacts primarily on the hippocampus‐dependent cognitive processes, we wondered whether HTyr could stimulate hippocampal neurogenesis in vivo in adult and aged wild‐type mice as well as in the B‐cell translocation 1 gene (Btg1) knockout mouse model of accelerated neural aging. We found that treatment with HTyr activates neurogenesis in the dentate gyrus of adult, aged, and Btg1‐null mice, by increasing survival of new neurons and decreasing apoptosis. Notably, however, in the aged and Btg1‐null dentate gyrus, HTyr treatment also stimulates the proliferation of stem and progenitor cells, whereas in the adult dentate gyrus HTyr lacks any proliferative effect. Moreover, the new neurons generated in aged mice after HTyr treatment are recruited to existing circuits, as shown by the increase of BrdU + /c‐fos + neurons. Finally, HTyr treatment also reduces the markers of aging lipofuscin and Iba1. Overall, our findings indicate that HTyr treatment counteracts neurogenesis decline during aging.